1980
DOI: 10.3109/01913128009141432
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Pathology of Tuberous Sclerosis in Children

Abstract: Ten cases of tuberous sclerosis involving the central nervous system (CNS) in children aged 2 days to 15 years were studied. The abnormal cells found in subependymal, cortical, and white matter lesions were examined by light and electron microscopy. Histochemistry and immunohistochemistry were also employed. The results were similar in all lesions. Approximately one-third of the abnormal cells were positive by glial fibrillary acidic protein (GFAP), one-half by Nissl, and one-quarter by Holzer's stains. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…[46][47][48] There is evidence for astrogliosis from histopathology in human TSC lesions, 8,49,50 but this has not been described in NAWM. Uhlmann et al 48 reported that heterozygosity for TSC2 resulted in a 1.5-fold increase in the numbers of astrocytes in mice in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] There is evidence for astrogliosis from histopathology in human TSC lesions, 8,49,50 but this has not been described in NAWM. Uhlmann et al 48 reported that heterozygosity for TSC2 resulted in a 1.5-fold increase in the numbers of astrocytes in mice in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…SENs are among the most common brain lesions associated with TSC (95% of the patients) and are contiguous with the lateral ventricles (LVs) (Bender and Yunis, 1980). SENs contain enlarged neurons and glia as well as giant or multinucleated cells similar to those observed in tubers.…”
Section: Subependymal Nodules (Sen) and Segamentioning
confidence: 99%
“…The underlying pathology, cortical tubers and subependymal giant cell astrocytomas (SEGAs), is characterized by focal disorganized arrays of dysplastic and proliferating cellular elements, most notably giant cells of indeterminate origin (17,18). Although early studies have shown a lower than expected frequency of loss of heterozygosity in brain lesions (19), recent immunoanalysis of SEGAs in TSC patients has confirmed the lack of tuberin expression within the spindle and epithelioid cells in these lesions (20).…”
mentioning
confidence: 99%